Servant leadership in crisis management: leadership response in the management of Covid-19 pandemic in Ghana - Kwame Asamoah; Emmanuel Kems Bigodza (Social Sciences and Humanities Open)
This paper examined the application of the servant leadership style–broadly defined as a leadership style that focuses on serving others and improving the lives of people, organizations, and communities-by President Akufo Addo in addressing the Covid-19 pandemic crisis in Ghana. The study employs a qualitative case study approach using content analysis to (1) analyze how servant leadership principles were applied in the management of the Covid-19 pandemic by President Akufo Addo, and (2) the effectiveness of servant leadership in crisis response and its potential implications for leadership theory and practice. The findings revealed that President Akufo Addo exhibited several key characteristics of the servant leadership approach throughout the period of the pandemic in Ghana. First, President Akufo Addo demonstrated persuasion and effective communication through regular updates to the public, explaining the situation and measures taken. Second, President Akufo engaged various stakeholders to coordinate the pandemic response. Third, the government implemented policies to support citizens' well-being' such as electricity subsidies and food distribution programs for vulnerable populations. In addition, early implementation of preventive measures such as school closures and gathering restrictions were rolled out during the pandemic. These findings revealed that President Akufo Addo's approach aligned closely with servant leadership principles that prioritize citizen welfare and the application of preventive and protective measures. These actions resulted in significant initiatives to mitigate pandemic risks, stabilize food security, and cushion the economic impact on basic services. This study fills the gap in current literature in the field of leadership responses by demonstrating the applicability and the effectiveness of the servant leadership style in crisis management within the specific context of the Covid-19 pandemic. It also extends our understanding of how servant leadership can be operationalized in response to complex and systemic challenges such as crisis.